How to live on the edge - Scheerger, Sarah Lynn 1975- (Minneapolis Carolrhoda Lab, 2020)
Eighteen-year-old Cayenne learns that her long-dead mother left her and her sister a series of video messages; that their aunt, who raised them, has the same gene mutation that caused their mother's cancer; and that she and her sister may also have it
Keywords: Breast -- Cancer -- Fiction; Death -- Fiction; Family life -- Fiction; Genetics -- Fiction; Sisters -- Fiction